Anticancer activity on mcf-7 and ssc-40 cancer cell lines using successive solvent extracts of Phyllanthus acidus [linn.] Leaves - VIJAY D. MENDHULKAR; ASHWINI S. SHINDE (International Journal of Pharma and Bio Sciences, 2017)
Phyllanthus acidus [Linn.] has diverse medicinal importance in Indian history and have high contents of Vitamin C. In terms of both variety and mechanism of action, medicinal plants provide an infinite source of anticancer drugs. The aim of the present study is to investigate cytotoxic potential of P. acidus leaves. Analysis is carried out by Successive Solvent Extraction (SSE) method using Petroleum Ether, Chloroform, Ethyl Acetate, Methanol and Aqueous as solvents. Total phenolic content (TPC) and total flavonoid content (TFC) was determined using gallic acid and quercetin, respectively as standards. The anti-proliferative activities of SSE were screened against two human cancer cell lines (Breast and Oral) representing different tissues using Sulforhodamine-B (SRB) assay. The results showed that the total flavonoid content (TFC) was highest (71.62 µg/ml) in methanol extract while, total phenolic content (TPC) was maximum (136.20 µg/ml) in Chloroform extract. The findings of SRB assay revealed that, Chloroform plant extract showed maximum anti-cancer properties against both Human Breast Cancer (MCF-7) andHuman Oral Cancer (SSC-40) Cell Line. While, Petroleum Ether, Ethyl acetate, Methanol and Aqueous plant extracts are cytotoxic only against MCF-7. These results indicate the potential of the medicinal herbs as chemopreventive agent and a good candidate for anti-neoplastic drug development. However, further studies are needed to isolate the active anti-cancer compounds responsible for this activity and evaluating their mode of action.